2019
DOI: 10.1002/adma.201901269
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Mechanical Properties of 3D Microstructures Using Visible Light Post‐Manufacturing

Abstract: the laser, where the square of the optical intensity exceeds the threshold needed to initiate polymerization. In this way, very small feature sizes of less than 100 nm can be achieved. [3,4] Microstructures pre pared via DLW have for example been used in microfluidic chips, [5,6] metama terials, [7] or as 3D microscaffolds for cell and tissue engineering. [8] Commercial resist mixtures are available that are well suited for the rapid generation of stable structures. However, when using standard resists, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…In addition to the photoresist selection and printing parameters' optimization, postprocessing of 2PP 3D-printed structures can contribute to achieving the desired material properties. For example, postprint curing can help improve the mechanical properties of hard polymers by increasing the degree of crosslinking, [99,100] thermal reflow can reduce surface roughness for fast printed structures, [101] and isotropic plasma etching and/or pyrolysis can be used to improve the resolution beyond 100 nm. [102]…”
Section: Light As Microrobot Builder: Two-photon Polymerizationmentioning
confidence: 99%
“…In addition to the photoresist selection and printing parameters' optimization, postprocessing of 2PP 3D-printed structures can contribute to achieving the desired material properties. For example, postprint curing can help improve the mechanical properties of hard polymers by increasing the degree of crosslinking, [99,100] thermal reflow can reduce surface roughness for fast printed structures, [101] and isotropic plasma etching and/or pyrolysis can be used to improve the resolution beyond 100 nm. [102]…”
Section: Light As Microrobot Builder: Two-photon Polymerizationmentioning
confidence: 99%
“…While the control of the degree of polymerization in the voxel during the actual writing process is of utmost importance for further improvements of DLW, it has been a challenge to directly measure the level of chemical conversion in the printed area. A few studies investigate the effect of the writing condition on the properties of the printed polymer network 28,[42][43][44][45][46] . By using different detection instrumentations, for non-commercial resists based on a mixture of two different tri-acrylates, a monomer conversion degree of 60%-75% has been obtained while for organic-inorganic hybrid resists, degree of conversion has been reported to be 35%-75% 42,43 .…”
Section: Characterization Of the Printed Polymer Networkmentioning
confidence: 99%
“…Recent developments in nano-scale devices take advantage of many complex patterns with high aspect ratio structures in its design 45,[53][54][55][56] . High strength along with high deformability is an essential property for the design and reliability of novel nano devices 57 .…”
Section: Stiffness Of the Printed Polymer Rodsmentioning
confidence: 99%
“…[40,41] However, we have recently observed that even the non-extended anthracene that is traditionally dimerized with highly energetic UV-light, can be efficiently brought to reaction with visible light up to 415 nm. [42] In order to induce the second folding step as well with mild visible light, the partially folded SCNP1 was irradiated in THF (0.25 mg mL -1 ) with a violet LED (centered at λ = 415 nm, emitting between λ = 390 nm and λ = 440 nm). The hydrodynamic volume of SCNP1 underwent a This article is protected by copyright.…”
Section: Wavelength Selective Activation Of the Anthracene Folding Pomentioning
confidence: 99%